Substantiation of Well-Known Trademarks in Indonesian Trademark Disputes: Legal Analysis and Case Study - Sudirman, Lu; Disemadi, Hari Sutra; Fitri, Winda; Tan, David (International Journal of Law Reconstruction, 2024)
Trademark protection is important because of its role in representing a brand’s integrity. The effort to protect trademark rights is therefore essential in ensuring that the brand’s integrity does not suffer any erosion, even if it means going for a lawsuit. This research is conducted to analyze the challenges in pursuing a lawsuit to protect trademark rights, particularly in proving what constitutes a well-known trademark. This research utilized the normative legal research method to analyze the existing positive law in Indonesia, particularly regarding the protection of trademarks. The conceptual analysis supported by the normative research method used in this research found that most of the literature favors the effort to protect trademarks, as it covers a significant portion of a brand’s strategy and perception in the public eye. However, the case study found that the reality of this pathway can be difficult, where there is a possibility that a decision can be made not based on a sound ratio decidendi, or even the lack thereof.